2020
DOI: 10.1097/gox.0000000000002943
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Partner Satisfaction in Predicting Patient Satisfaction Regarding Post-mastectomy Breast Reconstruction

Abstract: Background: Qualitative studies have suggested that perceived partner satisfaction is an important predictor of patient satisfaction in post-mastectomy breast reconstruction. To better characterize these relationships, a couple-based study employing a quantitative analysis was conducted. Methods: BREAST-Q and a novel partner survey were used to assess relationships among patient satisfaction, perceived partner satisfaction, and reported partner satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…The current ndings support the validity of these statements as their partners reported that the women experienced problems in the same direction. Similar ndings were described in a recent quantitative study including 11 breast cancer patients and their partners, speci cally that a strong positive correlation was observed between the partner and patient satisfaction with the aesthetic outcome of the breast reconstruction after mastectomy [30]. Subgroup analyses comparing women with and without a previous breast cancer diagnosis were not possible in this present study due to the small sample size.…”
Section: Discussionsupporting
confidence: 89%
“…The current ndings support the validity of these statements as their partners reported that the women experienced problems in the same direction. Similar ndings were described in a recent quantitative study including 11 breast cancer patients and their partners, speci cally that a strong positive correlation was observed between the partner and patient satisfaction with the aesthetic outcome of the breast reconstruction after mastectomy [30]. Subgroup analyses comparing women with and without a previous breast cancer diagnosis were not possible in this present study due to the small sample size.…”
Section: Discussionsupporting
confidence: 89%
“…10 Based on other's data as well as our own, we created a handout entitled, "Post-Mastectomy Breast Reconstruction: Tips for Supporting your Partner" which may be used as an additional resource for partners (Appendix 3). 15,18,20,22 Our current study demonstrates that our novel partner survey has an acceptable level of internal consistency, and thus, may be used as a viable option for assessing partner satisfaction with emotional relationship, partner's breasts, partner's medical care, and sexual relationship.…”
Section: Discussionmentioning
confidence: 78%
“…14 Data from this study supported the presence of a relationship between overall patient and partner satisfaction with post-mastectomy breast reconstruction. 15 Despite the strong correlation, notable discrepancies existed between patient and partner, speci cally with relation to post-operative sexual experience and understanding of appropriate post-operative expectations. 15 To further investigate the complex relationship between patient and partner experience, and ultimately satisfaction, with post-mastectomy breast reconstruction, we performed an extension of our pilot study, this time including both patients and partners who had undergone mastectomy alone or in combination with breast reconstruction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Data from this study supported the presence of a relationship between overall patient and partner satisfaction with postmastectomy breast reconstruction. 15 Despite the strong correlation, notable discrepancies existed between patient and partner, specifically with relation to postoperative sexual experience and understanding of appropriate postoperative expectations. 15 To further investigate the complex relationship between patient and partner experience, and ultimately satisfaction, with postmastectomy breast reconstruction, we performed an extension of our pilot study, this time including both patients and partners who had undergone mastectomy alone or in combination with breast reconstruction.…”
mentioning
confidence: 99%